Differential diagnosis between rheumatoid arthritis and psoriatic arthritis: the value of ultrasound findings at metacarpophalangeal joints level. Issue 6 (15th March 2011) - Gutierrez, Marwin; Filippucci, Emilio; Salaffi, Fausto; Di Geso, Luca; Grassi, Walter
Abstract : Objective: To investigate the potential of ultrasound (US) in the differential diagnosis between rheumatoid arthritis (RA) and psoriatic arthritis (PsA) at metacarpophalangeal (MCP) joints level. Methods: 18 RA patients and 20 PsA patients with clinical involvement of MCP joints were included. All US examinations were performed by two rheumatologists investigating: presence of joint cavity widening (JCW), synovial fluid and/or synovial hypertrophy, peritenon extensor tendon inflammation (PTI) and intra-articular or peri-tendinous power Doppler (PD) signal. Results: A total of 83 MCP joints in 18 RA patients were assessed. In all of these the authors found different degrees of JCW. 15 of 83 (18%) MCP joints showed synovial fluid, whereas 68 of 83 (82%) MCP joints showed synovial hypertrophy. In 72 of 83 (86.7%) MCP joints intra-articular PD was detected. No PTI pattern was found in these patients. In PsA patients, a total of 82 MCP joints in 20 patients were assessed. 54 of 82 (65.8%) MCP joints showed PTI pattern (p = 0.001). In 50 of these 54 (92.5%) MCP joints extra-articular PD signal was detected (p = 0.001). 28 of 82 (34.1%) MCP joints showed different degrees of JCW. 6 of 28 (21.4%) MCP joints presented synovial fluid, whereas 22 of 28 (78.5%) MCP joints showed synovial hypertrophy. In 8 of 82 (9.7%) MCP joints the JCW and PTI patterns were found contemporaneously. Conclusions: Preliminary results demonstrate that PTI pattern is a higher characteristic of PsA, which suggests a potential role of US in the differential diagnosis between RA and PsA at MCP joints level.